Dancing Motherhood (Taylor & Francis, 2023)
Dancing Motherhood explores how unique factors about the dance profession impact mothers working in it. Ali Duffy introduces the book by laying a foundation of social and cultural histories and trends leading to the issues mothers in dance negotiate today. This study then reveals perspectives from mothers in dance working in areas such as performance choreography, dance education, writing, and advocacy though survey and interview data. Based on participant responses, recommendations for changes in policy, hiring, evaluation, and other work practices to better support working mothers in dance are outlined and discussed. Finally, essays from five working mothers in dance offers more intimate, personal stories and guidance geared to mothers, future mothers, and colleagues and supervisors of mothers in the dance field. By describing lived experiences and offering suggestions for improved working conditions and self-advocacy, this book initiates expanded discussion about women in dance and promotes change to positively impact dancing mothers, their employers, and the dance field.
English
Keywords: Gender Studies, Dance, Motherhood, Parenting, LGBT studies; thema EDItEUR::A The Arts; thema EDItEUR::J Society and Social Sciences; thema EDItEUR::V Health, Relationships and Personal development